Clinical Characteristics and Risk Factors of Lung Cancer-Associated Acute Ischemic Stroke. (18th December 2019) - Lin, Jiacai; Wu, Siting; Xu, Rui; Shi, Qiang; Tian, Chenglin; Cui, Fang; Shao, Xue; Liu, Hui
Abstract : Objective . To research the clinical characteristics and risk factors of lung cancer-associated acute ischemic stroke (LCA-AIS). Methods . Patients diagnosed with LCA-AIS, simple lung cancer, and simple AIS were enrolled. The primary information, laboratory results, tumor histopathology, neurological deficits, and survival time of the patients were collected and analyzed. Results . (1) In the LCA-AIS group, the pathology of 69.56% patients were adenocarcinoma, and the proportion of poorly differentiated patients was significantly more than that in moderately differentiated or highly differentiated. The number of stage IV lung cancer patients in the LCA-AIS group was significantly more common than in other stages. (2) 56.52% of patients with lung cancer were diagnosed before AIS, and the peak of AIS attack was 1–6 months after the diagnosis of lung cancer. (3) The independent risk factors of LCA-AIS were CYFRA-211 (OR 1.070; 95% confidence interval 1.005, 1.139; p = 0.035 ), TT (OR 1.275; 95% confidence interval 1.089, 1.493; p = 0.003 ), and Hct (OR 0.878; 95% confidence interval 0.779, 0.990; p = 0.034 ), making ROC curve, suggesting the area under the curve is 0.871. (4) The neurological deficit of patients in the LCA-AIS group was similar to the simple AIS group and could not be identified by the severity of neurological deficits. (5) The median survival time of LCA-AIS group patients was five months (95% confidence interval 3.796, 6.204). There were statistical differences in survival time between LCA-AIS group and simple AIS group patients (p < 0.001 ). Conclusions . The interaction between lung cancer and AIS may shorten patients' life expectancy and worsen their quality of life.